The Analysis of Nursing Care for the Elderly with Hypertension Using the Practice of Progressive Muscle Relaxation Therapy: A Case Study - Susan Susyanti; Rizki Rahayu (Ruang Ide, 2022)
Background: Hypertension attacks more in middle age or the elderly. Non-pharmacological therapy is needed so that is safe and easy to apply in providing nursing care as an effort to control Hypertension in the elderly. Progressive Muscle Relaxation (PMR) therapy can be used as an effective and safe nursing action. Objective: This case study aims to analyze the application of progressive muscle relaxation therapy in providing nursing care for the elderly with hypertension. Methods: This study used a case study design. The participant was elderly with Hypertension. The instrument used was a sphygmomanometer and PMR as a systematic technique to achieve a state of relaxation, a method that is applied through the application of a progressive method with gradual and continuous exercise on skeletal muscles by tensing and relaxing them which can restore muscle feeling so that the muscles relax, in this study, for 3 days with a length of 15 minutes on each day. Results: This study uses a case study. The results showed that the change in blood pressure before and after being given PMR decreased, from 170/110 to 158/100 mm Hg. This also has an impact on all client complaints so that they can be resolved, although not completely. The application of PMR therapy in nursing practice can be used as an effort to control hypertension naturally. Conclusion: There is that PMR therapy can be applied in providing nursing care to the elderly with Hypertension because it is effective in lowering blood pressure.